“We Asked for Workers but Human Beings Came”: A Critical Assessment of Policies on Immigration and Human Trafficking in the European Union (2009)
Globalization has transformed migratory flows, immigration policies, and citizenship. This chapter examines the intractable challenges of migration and human trafficking from a new perspective: the politics of immigration characterized by restriction of entry, containment, and selection. It argues that globalization and the new immigration policies ensure that only an elite group of highly-skilled migrants enter the European Union (EU) while the poor are encouraged to stay in their own countries. At the same time, there is growing demand for cheap (skilled and unskilled) labor in catering, hotel, and seasonal employment through the back door which provides a market for human traffickers and allows unscrupulous employers to pay low wages. The chapter examines these developments as well as new employment legislations targeted at those who give jobs to those without papers.